الظاهر والباطن في تفسير القرآن (دراسة مقارنة بين الاتجاهين الصوفي والشيعي) - Mahran, Sultan (Jurnal Studi Al-Qur'an, 2026)
The diversity of interpretations of the Qur'an has played a significant role in enriching Islamic thought throughout history. Among the methods that have attracted attention are Sufi allegorical (ishārī) and Shia esoteric (bāṭinī) interpretations, both of which emphasize the revelation of the text's inner meaning. However, ambiguity often arises regarding the methodological similarities or differences between the two. This study aims to examine the fundamental differences between these two approaches and their implications for understanding the Qur'an. It addresses whether Sufi and Shia interpretations share a common methodological framework for accessing the inner meaning or follow different paths. A comparative analytical methodology is employed, drawing on classical exegetical sources from both traditions. Examples are analyzed based on consistent criteria, including linguistic context, theoretical foundations, and doctrinal assumptions. The results reveal a fundamental difference; Sufi interpretation is rooted in spiritual contemplation and symbolism, while Shia interpretation is tied to Imami doctrine. Therefore, it is recommended that Islamic studies scholars refrain from generalizing about the forms of esoteric interpretation and conduct further studies to explore how these differences influence inter-school dialogue in the modern era.